2019
DOI: 10.1101/gr.246082.118
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequencing reveals intra-species tolerance of substantial structural variations and new subtelomere formation in C. elegans

Abstract: Long-read sequencing technologies have contributed greatly to comparative genomics among species and can also be applied to study genomics within a species. In this study, to determine how substantial genomic changes are generated and tolerated within a species, we sequenced a C. elegans strain, CB4856, which is one of the most genetically divergent strains compared to the N2 reference strain. For this comparison, we used the Pacific Biosciences (PacBio) RSII platform (80×, N50 read length 11.8 kb) and generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(118 citation statements)
references
References 106 publications
11
107
0
Order By: Relevance
“…CB4856, isolated from a pineapple field in Maui in 1972, was for many years the C. elegans isolate most different from N2, and these two strains have been the subject of an enormous number of genetic studies. Both strains have exceptional highquality genome assemblies (Consortium 1998; Thompson et al 2015;Kim et al 2019;Yoshimura et al 2019). Population genetic studies have revealed that the similarity of most wild isolates to N2 results from very recent partial selective sweeps and migration events that have homogenized much of the species, while CB4856 retains alleles that were lost in the swept populations Andersen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CB4856, isolated from a pineapple field in Maui in 1972, was for many years the C. elegans isolate most different from N2, and these two strains have been the subject of an enormous number of genetic studies. Both strains have exceptional highquality genome assemblies (Consortium 1998; Thompson et al 2015;Kim et al 2019;Yoshimura et al 2019). Population genetic studies have revealed that the similarity of most wild isolates to N2 results from very recent partial selective sweeps and migration events that have homogenized much of the species, while CB4856 retains alleles that were lost in the swept populations Andersen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Since the three worm strains responded differently to the range of bacteria, we sought to characterize molecular polymorphisms in these conserved dauer-controlling pathways. N2 and CB4856 already had sequenced and assembled genomes ( Kim et al, 2019 ), so we sequenced JU1395’s genome to allow for comparisons between the three strains. The assembled sequence was 103,053,620 nucleotides in 161 contiguous pieces.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, analysis of the newly identified genomes of yeasts and C. elegans by long‐read sequencing showed that subtelomeres experienced significant changes including extensive SVs and interchromosomal reshuffling following telomere damage, even in the presence of the telomerase gene. [ 23,24,127 ]…”
Section: Long‐read Genome Sequencing Revealed Subtelomeric Structuresmentioning
confidence: 99%
“…Signatures of DSB repair have also been observed in subtelomeres of the two most divergent strains of C. elegans , CB4856 and N2. [ 24 ] In these strains, the right end of chromosome V contains the subtelomeric region with the largest difference; the Hawaiian CB4856 strain has a new sequence of ≈200 kb after the telomere of the Bristol N2 strain ( Figure 2 ). The newly added sequence starts with about one tenth of the telomeric repeat sequences of C. elegans average telomere length; this observation suggests that ancient telomere damage occurred that telomerase could not repair.…”
Section: Long‐read Genome Sequencing Revealed Subtelomeric Structuresmentioning
confidence: 99%
See 1 more Smart Citation